HYBRID METAHEURISTICS ALGORITHM BASED CONTROLLERS FOR WIRELESSHART NETWORKED CONTROL SYSTEMS - MIYA, HASSAN SABO (2018)
Recent advances in wireless technology have led to the emergence of industry standards such as WirelessHART. However, using it for control comes with a key challenge of handling stochastic network delays capable of degrading control performance. To address this, commonly used simple PID could be employed